Pulmonary granulomatosis of genetic origin. (29th April 2021) - Bode, Sebastian F.N.; Rohr, Jan; Müller Quernheim, Joachim; Seidl, Maximilan; Speckmann, Carsten; Heinzmann, Andrea
Granulomatous inflammation of the lung can be a manifestation of different conditions and can be caused by endogenous inflammation or external triggers. A multitude of different genetic mutations can either predispose patients to infections with granuloma-forming pathogens or cause autoinflammatory disorders, both leading to the phenotype of pulmonary granulomatosis. Based on a detailed patient history, physical examination and a diagnostic approach including laboratory workup, pulmonary function tests (PFTs), computed tomography (CT) scans, bronchoscopy with bronchoalveolar lavage (BAL), lung biopsies and specialised microbiological and immunological diagnostics, a correct diagnosis of an underlying cause of pulmonary granulomatosis of genetic origin can be made and appropriate therapy can be initiated. Depending on the underlying disorder, treatment approaches can include antimicrobial therapy, immunosuppression and even haematopoietic stem cell transplantation (HSCT). Patients with immunodeficiencies and autoinflammatory conditions are at the highest risk of developing pulmonary granulomatosis of genetic origin. Here we provide a review on these disorders and discuss pathogenesis, clinical presentation, diagnostic approach and treatment. Pulmonary granulomatosis of genetic origin mostly occurs in immunodeficiency disorders and autoinflammatory conditions. In addition to specific approaches in this regard, the diagnostic workup needs to cover environmental and occupational aspects. https://bit.ly/31SqdHW